Genetic testing can change diagnosis and treatment in children with congenital hypothyroidism - Cengiz Kara; Jamala Mammadova; Ümmet Abur; Cagri Gumuskaptan; Elif İzci Güllü; Ayhan Dağdemir; Murat Aydın (European Thyroid Journal, 2023)
Objective: Guidelines on congenital hypothyroidism (CH) recommend that genetic testing should aim to improve diagnosis, treatment or prognosis, but it is unclear which patients would benefit most from the genetic investigation. We aimed to i nvestigate the genetic etiology of transient CH (TCH) and permanent CH (PCH) in a well-characterized cohort, and thereby evaluate the impact of genetic testing on the management and prognosis of children with CH. Methods: A total of 48 CH patients with normal, goitrous (n = 5) or hypoplastic thyroid (n = 5) were studied by high-throughput sequencing using a custom-designed 23-gene panel. Patients initially categorized as TCH (n = 15), PCH (n = 26) and persistent hyperthyrotropinemia (PHT, n = 7) were re-evaluated after genetic testing. Results: Re-evaluation based on genetic testing changed the initial diagnoses from PCH to PHT (n = 2) or TCH (n = 3) and from PHT to TCH (n = 5), which resulted in a final distribution of TCH (n = 23), PCH (n = 21) and PHT (n = 4). Genetic analysis also allowed us to discontinue treatment in five patients with monoallelic TSHR or DUOX2, or no pathogenic variants. The main reasons for changes in diagnosis and treatment were the detection of monoallelic TSHR variants and the misdiagnosis of thyroid hypoplasia on neonatal ultrasound in low birthweight infants. A total of 4 1 (35 different, 15 novel) variants were detected in 65% (n = 31) of the cohort. These variants, which most frequently affected TG, TSHR and DUOX2, explained the genetic etiology in 46% (n = 22) of the patients. The molecular diagnosis rate was significantly hig her in patients with PCH (57%, n = 12) than TCH (26%, n = 6). Conclusions: Genetic testing can change diagnosis and treatment decisions in a small proportion of children with CH, but the resulting benefit may ou tweigh the burden of lifelong follow-up and treatment.